Preliminary Efficacy Report and Prognosis Analysis of Endoscopic Endonasal Nasopharyngectomy for Recurrent Nasopharyngeal Carcinoma - Peng, Zhouying; Wang, Yumin; Wang, Yaxuan; Fan, Ruohao; Gao, Kelei; Zhang, Hua; Xie, Zhihai; Jiang, Weihong (Frontiers in Surgery, 2021)
Background: Compared with radiotherapy, endoscopic endonasal nasopharyngectomy (EEN) is increasingly used to treat recurrent nasopharyngeal carcinoma (NPC) because of its good prognosis and mild complications. This study aims to investigate the efficacy of EEN in the treatment of recurrent NPC and factors affecting prognosis. Methods: This study included all patients who received EEN for recurrent nasopharyngeal carcinoma from April 2016 to April 2020. All operations were performed in Xiangya Hospital Central South University. The patient's 2-year overall survival (OS) rate, disease-free survival (DFS) rate and significant prognostic factors are reported. Results: There were 38 (67.9%) males and 28 (32.1%) females, with a median age of 43 (range, 24–69 years).43 (76.8%) of the patients in our study were in advanced rT3-rT4 stage and 32 (74.4%) of the patients in the advanced stage had tumor growth closely related to the internal carotid artery (ICA). During a mean follow up period of 44 month (range 1–65 months) post-surgery. The 2-year OS rate was 48.6%, 2-year DFS rate was 42.6%. The 2-year OS rates of rT1-2 and rT3-4 recurrent NPC were 83.9 and 35.6%, respectively. The 2-year DFS rates of rT1-2 and rT3-4 recurrent NPC 76.2 and 56.3%. The advanced T stage were associated with a poor prognosis in terms of OS and DFS. Conclusions: Data indicate that T staging may be an independent prognostic factor for OS and DFS. Through proper preoperative evaluation, EEN is an alternative treatment option for advanced recurrent NPC that ensures a certain level of efficacy and is relatively safe with few complications. However, additional studies with long-term follow-up and a larger sample size are required.